2023
DOI: 10.24057/2071-9388-2022-098
|View full text |Cite
|
Sign up to set email alerts
|

Contribution Of The Different Sources To The Formation Of Alluvial Sediments In The Selenga River Delta. (Eastern Siberia, Russia)

Abstract: Unraveling sources of sediment supply, their temporal and spatial variability is of key importance to determine origin of deposits and to explore the formation mechanism of Selenga Delta landscape units. From an environmental point of view this solution would help to identify the particle-bound pollution sources. We used geochemical fingerprinting (the FingerPro R package), which is a modern quantitative implementation of the method of sedimentary provenance analysis. The main aim was to recognize the main pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…To assess the quality of water and phthalate content in the Selenga River and its delta, samples of surface water (n = 118) were taken from a depth of 0.2-0.5 m at the following sampling sites: in the Selenga River [upstream of Ulan-Ude (1); downstream of Ulan-Ude, at the right (2) and left (3) banks of the Selenga River; at the beginning of the delta-a point downstream of Kabansk (4)], and in the estuarine areas of the Selenga River [Levoberezhnaya (5), Kharauz (6), Galutai (7), Srednyaya (8), Severnaya (9), Lobanovskaya (10)] (Figure 1).…”
Section: Study Area and Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the quality of water and phthalate content in the Selenga River and its delta, samples of surface water (n = 118) were taken from a depth of 0.2-0.5 m at the following sampling sites: in the Selenga River [upstream of Ulan-Ude (1); downstream of Ulan-Ude, at the right (2) and left (3) banks of the Selenga River; at the beginning of the delta-a point downstream of Kabansk (4)], and in the estuarine areas of the Selenga River [Levoberezhnaya (5), Kharauz (6), Galutai (7), Srednyaya (8), Severnaya (9), Lobanovskaya (10)] (Figure 1).…”
Section: Study Area and Samplingmentioning
confidence: 99%
“…The river water enters Lake Baikal with a significant amount of dissolved and suspended terrigenous material. This material is mostly deposited at the river mouth, forming a classic delta with an area of approximately 600 km 2 [7,8]. The floodplain and soils in the riverine areas, together with the associated aboveground and aquatic vegetation, serve as a geochemical barrier safeguarding the waters of Lake Baikal.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore the knowledge of sediment origin can be crucial for sustainable management planning (Walling 2005). The research by Zaharova and Belyaev (2022) was conducted using the geochemical fingerprinting method, which uses a quantitative approach to determine sediment origin and associated pollution. Using this method, they found that the majority of sediment on the floodplains of the delta was sourced from floodplains and terraces slopes, and only a small amount originated from remote areas.…”
Section: Sediment Transport and River Morphologymentioning
confidence: 99%